Studi pemanfaatan condensate outlet steam trap sebagai air umpan boiler di Pabrik Amoniak Pusri-IB - Alfa Widyawan; Ferlyn Fachlevie (Jurnal Rekayasa Proses, 2013)
As ammonia and urea producer, PT. Pusri consumes a lot of steam, which is used as raw material in ammonia plant, as well as heating medium and turbine driving agent. Steam pressure used in the P-IB Ammonia plant varies from 3.5 to 123 kg/cm2gauge. Distribution system of steam piping to the equipments causes heat loss to the environment. This leads to the production of steam condensate flowing along the pipe. The steam condensate from the pipe (through the steam trap) is directly discharged into the sewer. The present study aimed to determine the rate of steam condensation and to elaborate an economic feasibility to utilize the condensate as boiler feed water in the Ammonia plant P-IB.Calculation of heat transfer in the pipes was based on the principles of conduction, convection and radiation. The rate of steam condensation was calculated with steam pressure variation from 3.5 to 123 kg/cm2gauge, pipe diameter from 4 to 20-inch and insulation thickness of 1 to 4 inches. The rate of condensation was expressed in a mathematical equation and was a function of insulation thickness and diameter of pipe.The results showed that the rate of steam condensation rised as steam pressure and pipe diameter increased and insulation thickness decreased. Operating cost reduced if the steam condensate was used as boiler feed water replacing demineralized water. This also caused reduction of fuel consumption and therefore resulted in simple payback period of 0.9 years.